Effect of Co substitution on the magnetic and electron-transport properties of Mn2PtSn. (28th January 2015) - Huh, Y; Kharel, P; Nelson, A; Shah, V R; Pereiro, J; Manchanda, P; Kashyap, A; Skomski, R; Sellmyer, D J
Abstract: The structural, magnetic and electron-transport properties of Mn2 Pt1− x Co x Sn( x  = 0, 0.3, 0.5, 0.7, 1) ribbons prepared by arc-melting and melt-spinning were investigated. The rapidly quenched alloys with x  = 0 and 0.3 were found to crystallize in the inverse tetragonal structure, but the structure transformed into inverse cubic as x increased to 0.5. At room temperature, the samples are ferro or ferrimagnetic, and the Curie temperature increases by 225 K from 370 K for Mn2 PtSn ( x  = 0) to 595 K for Mn2 CoSn ( x  = 1). The measured anisotropy constants for the inverse-tetragonal alloys are on the order of 1 Merg cm −3 at room temperature. The ribbons are moderately conducting with the room temperature resistivities being between 0.4 and 8.4 mΩ cm. Interestingly, the thermal coefficient of resistivity transforms from positive to negative and the magnetoresistance transforms from negative to positive as the value of x reaches 0.5.